Efficacy of neck-mounted lazy holder for smartphones on cervical pain and function in patients with non-specific neck pain - Omnia Mohamed Mohamed Abdel Moneim; Ragia Mohamed Kamel; Mohamed Ibrahim Abdelhay (Bulletin of Faculty of Physical Therapy)
Abstract Background Non-specific neck pain (NSNP) is characterized by pain, stiffness, functional limitation impacting overall quality of life. Strongly associated nowadays with smartphone usage posture. The study aimed to explore clinical benefits of addressing daily postural habits by integrating an ergonomic accessory called neck-mounted smartphone holder. Methods The study included 40 patients aged 18–45 years diagnosed with NSNP who used a smartphone at least 6 h a day, recruited from the outpatient clinics of faculty of physical therapy at Benha University and they were randomly allocated to two equal groups. Both received conventional exercise in the form of isometric strength and stretch exercises for three weekly sessions over 4 weeks. The study group was instructed additionally to use the holder daily during smartphone use. Measured outcomes were numeric pain rating scale (NPRS), neck Bournemouth questionnaire (NBQ), cervical range of motion (CROM) and pain pressure threshold of neck muscles (PPT). Two measurements were taken, first at baseline, second after the end of 12th session. The study confirmed normality (Shapiro–Wilk) and variance homogeneity (Levene’s), used unpaired t-tests for demographic comparisons, and applied mixed-design MANOVA (SPSS v23) with follow-up ANOVAs and Bonferroni-corrected post-hoc tests (α = 0.05) to assess treatment effects on outcomes. Results However, both groups showed significant difference post intervention, greater improvement was reported in the study group in terms of pain (NPRS: 77% vs. 46%), function (NBQ: 78% vs. 42%) and cervical mobility as flexion (20% vs. 5%), extension (40% vs. 20%), side bending (right: 26% vs. 13%; left: 24% vs. 10%), and rotation (right: 36% vs. 12%; left: 42% vs. 22%). PPT at suboccipital point (right: 70% vs.14%; left: 68% vs. 23%), levator scapula (right 58% vs. 13%; left: 60% vs. 22%), and upper trapezius (right: 39% vs. 13%; left: 34% vs. 16%). MANOVA revealed significant group, time, and interaction effects (ƞ2 = 0.92–0.99, p < 0.001). Conclusion Adding smartphone holders to conventional exercises had greater effect on neck pain, functional mobility, and quality of life in patients with NSNP. AS aligned with previous research, holistic management of neck pain and addressing daily habits as behavioral and environmental modification showed greater improvement. Trial registration This study was registered on ClinicalTrials.gov (ID: NCT06767098) under title “Efficacy of New Ergonomic Device in Non-Specific Neck Pain” on 5 January 2025, retrospectively registered.